2022
DOI: 10.1017/s0022149x22000682
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasite community structure of an anuran assemblage in the Caatinga, Northeastern Neotropical Region

Abstract: Amphibians are a widespread Chordata taxon and are important for maintaining the balance of both terrestrial and aquatic ecosystems. Brazil has a rich amphibian fauna; however, little is known about the role of their ecology and phylogenetic relationships during the assembly processes of associated endoparasite communities. Herein, we describe an endoparasite community in an anuran assemblage in the Caatinga, a unique biome of dry forests in north-eastern Brazil. We studied endoparasite diversity, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Janovy et al (1992) state that the presence of a parasitic species in a host species is strongly influenced by evolutionary factors. However, the infection data obtained in the present study suggest an ecological influence on the observed infection pattern, corroborating the studies by Sampaio et al (2022) and Oliveira et al (2023). In the case of acanthocephalans, hosts from a given locality are probably more related ecologically due to similarities in diet and habitat than phylogenetically (McAlpine 1997;Kennedy 2006), which should explain the presence of Centrorhynchus sp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Janovy et al (1992) state that the presence of a parasitic species in a host species is strongly influenced by evolutionary factors. However, the infection data obtained in the present study suggest an ecological influence on the observed infection pattern, corroborating the studies by Sampaio et al (2022) and Oliveira et al (2023). In the case of acanthocephalans, hosts from a given locality are probably more related ecologically due to similarities in diet and habitat than phylogenetically (McAlpine 1997;Kennedy 2006), which should explain the presence of Centrorhynchus sp.…”
Section: Discussionsupporting
confidence: 91%
“…However, the infection data obtained in the present study suggest an ecological influence on the observed infection pattern, corroborating the studies by Sampaio et al . (2022) and Oliveira et al . (2023).…”
Section: Discussionmentioning
confidence: 95%